The Constituents of Michelia compressa var. formosana and Their Bioactivities - Chan, Yu-Yi (MDPI, 2014)
Phytochemical investigation of the heartwood of Michelia compressa afforded forty-four compounds, which were identified by comparison of experimental and literature analytical and spectroscopic data. Some compounds were evaluated for their anti-inflammatory and anticancer bioactivities. The result showed that soemerine (1) and cyathisterol (2) exhibited significant nitric oxide (NO) inhibition, with IC(50) values of 8.5 ± 0.3 and 9.6 ± 0.5 µg/mL, respectively. In addition, liriodenine (3) and oliveroline (4) exhibited cytotoxicity to human nasopharyngeal carcinoma (NPC-TW01), non-small cell lung carcinoma (NCI-H226), T cell leukemia (Jurkat), renal carcinoma (A498), lung carcinoma (A549) and fibrosarcoma (HT1080) cell lines with IC(50) values in the range of 15.7–3.68 μM.